PRODUKTIVITAS INDUK SAPI BALI DI BALAI PEMBIBITAN TERNAK UNGGUL SAPI BALI - , LUIS TAVARES ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aimed to identify the reproduction rate, pre-weaning growth rate and factors affecting the productivity of Bali cows at the Livestock Breeding Centre of Excellence for Bali Cattle (BPTU) in 2010-2011. The research used 130 Bali cows, and it was a survey method-based descriptive analytical research. Results showed that in terms of cow performance, the calf crop recorded 64.62%, mortality 5.95%, calving interval 11.36 ± 1.05 months, and cows parity 3.51 ± 2.01 heads. While in terms of the performance of pre-weaning growth, the birth weights of male and female calves were 18.37±1.65 kg and 18.27±1.20 kg, respectively. The weaning weights of male and female calves were 93.53 ± 21.00 kg and 87.66 ± 12.04 kg, respectively, with weaning time of 205 days. The average of pre-weaning daily weight gains were 0.37±0.10 kg/head/day and 0.34±0.06 kg/head/day for male and female calves, respectively. The reproduction rate and productivity rate of cows were 61.98% and 56.15 kg/cow/year. Based on statistical analysis, it was concluded that the productivity rate of cows and pre-weaning growth rate among Bali cows at the BPTU Bali in 2010-2011 were moderately high. Such a moderately higher productivity rate was affected by the tight selection factor on cows based on performance test and progeny test.